Children's literature in the digital world: How does multimodality support affective, aesthetic and critical response to narrative?. Issue 1 (5th May 2015) - Simpson, Alyson; Walsh, Maureen
Abstract : Purpose: – This paper aims to interrogate the place of literature in the digital world and the way a narrative is represented in digital spaces. In the changing landscape of digital, mobile and virtual texts, the authors aimed to examine how multimodal and animated elements in digital narratives engage young readers and encourage affective and aesthetic reader response? Design/methodology/approach: – The study was an exploratory, interpretive qualitative research study undertaken in a classroom of 28 10-year-old boys in grade 5. The investigators analysed data recorded during a lesson where students responded to the textual conventions and literary features of a traditional story read in print and multimodal digital format. Two coding systems were used to identify students' understanding of textual conventions along with the nature of their responses. Findings: – The results suggested that when students are prompted to attend to the impact of multimodal layering in digital literature, affective, aesthetic and critical responses, they are encouraged in their interpretations. The responses emphasised the importance of teacher scaffolding and development of meta-language in teaching literature in both print and digital form. Research limitations/implications: – Because of the small sample and limited data set, the research results lack generalisability. Therefore, researchers are encouraged to test the proposed implications further. Practical implications: – The paper includes implications for teacher pedagogy, while teaching reading with multimodal narratives in digital form. Originality/value: – This paper offers insight into the differences between print and multimodal literary texts; it codes students' responses to multimodal texts and offers a method for analysis.